Management of presumed candida endophthalmitis during the COVID-19 pandemic: Case report and review of the literature. Issue 3 (May 2023) - Fossataro, Federica; Martines, Francesco; Neri, Piergiorgio; Allegri, Pia; Pece, Alfredo
Purpose: To report the management of a case of candida endophthalmitis following intubation for SARS-CoV-2 ARDS, during the first lockdown, underlining consequently the limited access to the gold standard of care. Methods: Case report. Results: We have described the case of a 56-year-old Hispanic man who developed bilateral Candida endophthalmitis after one month of hospitalization in the intensive care unit for severe SARS-CoV-2 pneumonia. Multimodal imaging was obtained. Full serological screening for infection was done resulting negative. A diagnostic vitrectomy was impossible due to the limited access at the surgery room. Diagnosis of presumed candida endophthalmitis was made, according to a highly qualified center, and therapy with intravenous liposomal amphotericin B was administered. At three months, we observed lack of vitreous opacities and atrophic scars with no active lesions. Conclusions: Diagnosis of candida endophthalmitis was a challenge in this pandemic scenario, given the impossibility of performing a diagnostic vitrectomy. Therefore, it was mainly based on patient's clinical manifestations, multimodal imaging and on unanimity of collegiality between our hospital and the highly specialized center.